Monitoring and Analysis of Permafrost Deformation in Qilian mountains on Qinghai-Tibet Plateau Based on InSAR Data - Lu, Liang (The University of Edinburgh, 2024)
Permafrost, a critical component of the cryosphere, significantly influences global climate, environmental sustainability, and human activities. This study examines permafrost dynamics on the Qinghai-Tibet Plateau (QTP) using multitemporal interferometric synthetic aperture radar (InSAR) observations. We employed the LiCSBAS tool to analyze surface deformation data, generating average velocity and seasonal amplitude maps. Correlation analyses were conducted with environmental predictors such as soil properties, climate variables, and terrain characteristics. The results reveal significant spatial variations in permafrost dynamics, influenced by active layer thickness (ALT), mean annual ground temperature (MAGT), elevation, permafrost zonation index (PZI), and volumetric water content (VWC). The study underscores the link between permafrost and hydrological systems, highlighting the importance of meticulous preprocessing and high-resolution data for robust analytical outcomes. Despite computational constraints and reliance on line-of-sight (LOS) data, the insights gained provide a foundational framework for future research. This work emphasizes the need for advanced data processing techniques and high-resolution datasets in permafrost studies, contributing to a deeper scientific understanding and guiding future research methodologies.